Sei sulla pagina 1di 5

# Math 232 (Winter 2007) Assignment #3

## Q1. Find the general solution of the equation

dy
+ y 2 = y.
dt
Solution: The equation can be written as
1 dy
=1
y y 2 dt
and is thus separable. For y y 2 6= 0 (that is, for y 6= 0 and y 6= 1) , we compute


Z
Z
Z 
y
1
1
1
1
.

dy =
dy =
+
dy = ln |y| ln |1 y| = ln
y y2
y(1 y)
y 1y
1 y

## Thus, we can write the equation as

By integration, we get

y(t)
d
) = 1.
(ln
dt 1 y(t)

y(t)
= t + c,

ln
1 y(t)

## where c is a constant of integration. Taking exponential of each side and denoting C := e c ,

we get

y(t)
t

1 y(t) = Ce ,
which can be rewritten as

y(t)et

1 y(t) = C.

Since the function inside the absolute value sign is continuous, we can use the Intermediate
Value Theorem to deduce that
y(t)et
= C,
1 y(t)
which give us

Cet
.
(0.1)
1 + Cet
Now, we must also check if there are other (missing) solutions). Since the right-hand
side of the differential equation is zero when either y(t) = 0 or y(t) = 1 for all t, and
the derivative of a constant is zero, we deduce that these are also solution of the given
differential equation (they satisfy the equation for all t). Thus, the general solution is
y(t) =

2
given by (0.1), together with y(t) = 0, and y(t) = 1 for all t.
Q2. Find the solution to the initial value problem
dy
2t
=
;
dt
y + yt2

y(2) = 3.

y

2t
dy
=
.
dt
1 + t2

## This is straightforward. We can write this equation as

2t
d y 2 (t)
(
)=
dt 2
1 + t2
and by integration, we get
y 2 (t)
=
2

2t
dt + c = ln(1 + t2 ) + c.
1 + t2

Notice that, since 1 + t2 is always positive (for real t), we do not need the absolute value
sign. The general solution is therefore given by
p
p
y(t) = 2 ln(1 + t2 ) + c = ln(1 + t2 ) + C,

where C = 2c. Since the initial condition is, y(2) = 3, we use the above expression with
the positive sign to get C = 9 2 ln 5. Substituting this back in the expression above, the
solution to the given initial value problem is given by
s


1 + t2
.
y(t) = 9 + 2 ln
5
Q3. Find the general solution of the equation
dy
t2 y 2
=
.
dt
3ty
Solution: This equation is not linear or separable. Lets check whether the right hand
side is a function of y/t. For a 6= 0, we compute
(at)2 (ay)2
a2 (t2 y 2 )
t2 y 2
=
=
3(at)(ay)
3a2 ty
3ty

## Math 232 (Winter 2007) Assignment #3

and thus, the right hand side is indeed a function of y/t. Using the substitution y = vt
we can rewrite the given equation as
t

dv
t2 (v 2 t2 )
1 v2
+v =
=
dt
3t2 v
3v

t
which is

dv
1 v2
1 4v 2
=
v =
,
dt
3v
3v

(0.2)

1
3v dv
= .
1 4v 2 dt
t

## This is a separable equation, so (for 1 4v 2 6= 0), we first find the antiderivative of

Z

3
3v
dv =
2
1 4v
8

3v
.
14v 2

8v
3
dv = ln |1 4v 2 |.
2
1 4v
8

## The differential equation involving v can therefore be written as

d
3
1
( ln |1 4v 2 |) = .
dt 8
t
Integrating, we get

which gives us

3
ln |1 4v 2 | = ln |t| + c
8

ln t(1 4v 2 )3/8 = c

Taking the exponential of each side, denoting c1 := ec , and using the Intermediate Value
Theorem, we get
t(1 4v 2 )3/8 = c1
Now, we know that v = y/t. Therefore, we have
t(1 4

y 2 3/8
) = c1 ,
t2

## which, after some simplification gives us

(t2 4y 2 )3 t2 = C

(0.3)

where C is a suitably defined constant. We must also check what happens when 1 4v 2
is zero. It is easy to see that v(t) = 21 and v(t) = 12 are both solutions of (0.2). Using
the substitution y = vt, it can again be checked that y(t) = 2t and y(t) = 2t are each

4
solutions. These, together with (0.3) constitute the general solution.
Q4. Find the general solution of the equation
dy
y
1
2 = .
dt
t
ty
Solution: The equation can be written as
dy
y
1
2y 2 + 1
=2 +
=
dt
t
ty
ty
which is a separable equation. We write it as
y
dy
1
= .
1 + 2y 2 dt
t
We calculate
Z

y
1
dy =
1 + 2y 2
4

4y
1
dy = ln(1 + 2y 2 ) = ln(1 + 2y 2 )1/4 .
1 + 2y 2
4

## The equation can therefore be written as

d
1
(ln(1 + 2y 2 (t))1/4 ) = ,
dt
t
which, by integration gives
ln(1 + 2y 2 (t))1/4 = ln |t| + c.
Taking exponentials on each sides and writing c1 := ec , we get
(1 + 2y 2 (t))1/4 = c1 |t|,
or
y(t) =
where C = c41 .

1
(Ct4 1).
2

Q5. In 1980 the Department of Natural Resources released 1000 splake (a crossbreed of
fish) into a lake. In 1987, the population of splake in the lake was estimated to be 3000.
Using the Malthusian law for population growth, estimate the population of splake in the
year 2010.
(Note that the Malthusian law for population is given by
dp(t)
= ap(t),
dt

## where p(t) is the population at time t and a is the growth rate.)

Solution: . The solution to the initial value problem
dp
= ap ;
dt

p(t0 ) = p0

is
p(t) = p0 ea(tt0 )
We are given that the initial population is p(1980) = 1000 and that p(1987) = 3000. We
therefore have
3000 = 1000ea(19871980) ,
from which, we get that a =

1
7

ln 3. Therefore,
1

30

ln 3

' 110867.